A Review of 11 Cases of Obturator Hernia Repaired with Synthetic Mesh Using an Extra-Preperitoneal Approach - Yoshizawa, Junichi; Nakamura, Manabu; Ishizaka, Katsuhiko; Shibata, Hitoshi (The Japanese Journal of Gastroenterological Surgery, 2011)
We assessed 11 cases of mesh repair for obturator hernia using a midline extra-peritoneal approach. The Howship-Romberg sign and intestinal obstruction symptoms were recognized in 7 cases in each. The period from onset to operation was 12 hours to 7 days. To cover the obturator foramen, we used mesh sheets in 10 cases and a Kugel patch in 1 case. We repaired both sides of the obturator foramen in all cases. There were 7 cases of incarcerated small intestine, and 5 cases of resection of the intestine. We were able to prevent synthetic mesh infection by adequate washing and drainage of the preperitoneal cavity. The complications were 1 case of ileus, aspiration pneumonia and wound disruption, respectively, with no recurrences. The midline extra-peritoneal approach is useful to observe the bilateral obturator foramen and the operative field, with a minimum incision of the peritoneum at laparotomy, and peeling away a layer to lay down mesh to cover the obturator canal.